Palliative care delivery according to age among metastatic breast cancer patients. ESME-MBC cohort. (30th September 2020) - Frasca, M; Courtinard, C; Bouleuc, C; Levy, C; Mouret-Reynier, M A; Bachelot, T; Goncalves, A; Perotin, V; Eymard, J C; Mathoulin-Pelissier, S
Abstract: Background: Metastatic breast cancer (MBC) may require inpatient palliative care (IPC) but literature suggests age-related disparities in palliative care delivery. This study, based on real-world data, aimed to assess the cumulative incidence function (CIF) of IPC delivery and if age is an independent factor, taking into account the competing risk of death. Methods: The national multicenter ESME (Epidemio-Strategy-Medical-Economical)-MBC cohort includes consecutive MBC patients treated in the 18 French Comprehensive Cancer Centers. IPC identification used ICD-10 palliative care coding. Main analysis first estimated pseudo values of 2-year and 8-year CIF of IPC. Linear regression models estimated the mean changes of pseudo-values (2 models: 2-year and 8-year CIF of IPC). Results: Our analysis included 12375 patients, 5093 (41.2%) of whom were aged 65 or over. The median follow-up was 41.5 months (95% CI, 40.5-42.5). The CIF of IPC was 10.3% (95% CI, 10.2-10.4) and 24.8% (95% CI, 24.7-24.8) at two and eight years, respectively. At two years, among triple-negative patients, young patients (<65 yo) had a higher CIF of IPC than older patients after adjusting for cancer characteristics, centre, and period (65+/<65: β=-0.05; 95% CI, -0.08 to -0.01). Among other tumour subtypes, older patients received short-term IPC more frequently than young patients (65+/<65: β = 0.02; 95% CI, 0.01 to 0.03). At eight years, outside large centres, IPC was delivered less frequently to older patients adjusted to cancer characteristics and period (65+/<65: β=-0.03; 95% CI, -0.06 to -0.01). Conclusions: We found a relatively low CIF of IPC and that age influenced IPC delivery. Young triple negative and older non-triple negative patients needed more short-term IPC. Older patients diagnosed outside large centres received less long-term IPC. These findings highlight the need for a wider implementation of IPC facilities and for more age-specific interventions. Key messages: Our study highlighted particular challenge for older MBC patients diagnosed outside large French Comprehensive Cancer Centers. By identifying age at MBC diagnosis as a factor of IPC delivery, this report supports a wider implementation of IPC facilities and more age-specific interventions.